2020
DOI: 10.1177/0269216320908488
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported symptoms and problems at admission to specialized palliative care improved survival prediction in 30,969 cancer patients: A nationwide register-based study

Abstract: Background: Large, nationally representative studies of the association between quality of life and survival time in cancer patients in specialized palliative care are missing. Aim: The aim of this study was to investigate whether symptoms/problems at admission to specialized palliative care were associated with survival and if the symptoms/problems may improve prediction of death within 1 week and 1 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
(150 reference statements)
0
10
0
Order By: Relevance
“… Of the 16 studies included in the systematic review regarding cancer and PC, nine studies looked at referral criteria, and six studies evaluated referral outcomes. Five studies were prospective [ 24 – 28 ], four were retrospective [ 29 32 ], five were cross-sectional surveys [ 33 37 ], and two randomized controlled trials [ 28 , 38 ] ( Table 3 Palliative/Supportive Care in Cancer Patients Study Population Aims Design Key Findings Sanders, et al 2010. 109 patients with lung cancer To characterize the prevalence and intensity of supportive care needs and interest in specific supportive care services among individuals with lung cancer Cross-sectional survey Participants reported the greatest need in the physical and daily living domain, followed by psychological needs, health system and informational needs, and patient care support needs.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Of the 16 studies included in the systematic review regarding cancer and PC, nine studies looked at referral criteria, and six studies evaluated referral outcomes. Five studies were prospective [ 24 – 28 ], four were retrospective [ 29 32 ], five were cross-sectional surveys [ 33 37 ], and two randomized controlled trials [ 28 , 38 ] ( Table 3 Palliative/Supportive Care in Cancer Patients Study Population Aims Design Key Findings Sanders, et al 2010. 109 patients with lung cancer To characterize the prevalence and intensity of supportive care needs and interest in specific supportive care services among individuals with lung cancer Cross-sectional survey Participants reported the greatest need in the physical and daily living domain, followed by psychological needs, health system and informational needs, and patient care support needs.
…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 studies included in the systematic review regarding cancer and PC, nine studies looked at referral criteria, and six studies evaluated referral outcomes. Five studies were prospective [ 24 – 28 ], four were retrospective [ 29 32 ], five were cross-sectional surveys [ 33 37 ], and two randomized controlled trials [ 28 , 38 ] (…”
Section: Resultsmentioning
confidence: 99%
“…The studies on prognosis performed in palliative care aim to determine how short survival seems. 4 Some even try to find signs of impending death. 5 Palliative care services (PCS) are often overwhelmed by admission requests, and there is a need to establish priorities, and the expected survival can be crucial in the decision process.…”
Section: Introductionmentioning
confidence: 99%
“…The related literature has shown PS to be a reliable indicator of survival outcomes in cancer patients [ 8 , 9 ]. Numerous studies have demonstrated that PS evaluations along with clinical symptoms and signs can improve survival prediction in cancer patients [ 4 , 10 , 11 , 12 ]. PS has also been frequently employed as a criterion for evaluating a patient’s suitability for participation in clinical trials and modifying treatment strategies [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%